Stem Cells from Dental Pulp: What Epigenetics Can Do with Your Tooth - Rodas-Junco, Beatriz A.; Canul-Chan, Michel; Rojas-Herrera, Rafael A.; De-la-Peña, Clelia; Nic-Can, Geovanny I. (Frontiers in Physiology, 2017)
Adult stem cells have attracted scientific attention because they are able to self-renew and differentiate into several specialized cell types. In this context, human dental tissue-derived mesenchymal stem cells (hDT-MSCs) have emerged as a possible solution for repairing or regenerating damaged tissues. These cells can be isolated from primary teeth that are naturally replaced, third molars, or other dental tissues and exhibit self-renewal, a high proliferative rate and a great multilineage potential. However, the cellular and molecular mechanisms that determine lineage specification are still largely unknown. It is known that a change in cell fate requires the deletion of existing transcriptional programs, followed by the establishment of a new developmental program to give rise to a new cell lineage. Increasing evidence indicates that chromatin structure conformation can influence cell fate. In this way, reversible chemical modifications at the DNA or histone level, and combinations thereof can activate or inactivate cell-type-specific gene sequences, giving rise to an alternative cell fates. On the other hand, miRNAs are starting to emerge as a possible player in establishing particular somatic lineages. In this review, we discuss two new and promising research fields in medicine and biology, epigenetics and stem cells, by summarizing the properties of hDT-MSCs and highlighting the recent findings on epigenetic contributions to the regulation of cellular differentiation.